2021
DOI: 10.1038/s42003-021-02521-3
|View full text |Cite
|
Sign up to set email alerts
|

Auto-inhibitory intramolecular S5/S6 interaction in the TRPV6 channel regulates breast cancer cell migration and invasion

Abstract: TRPV6, a Ca-selective channel, is abundantly expressed in the placenta, intestine, kidney and bone marrow. TRPV6 is vital to Ca homeostasis and its defective expression or function is linked to transient neonatal hyperparathyroidism, Lowe syndrome/Dent disease, renal stone, osteoporosis and cancers. The fact that the molecular mechanism underlying the function and regulation of TRPV6 is still not well understood hampers, in particular, the understanding of how TRPV6 contributes to breast cancer development. By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Later, Cai et al (2021) proposed R492 to interact with D580, imposing autoinhibitory effects on the channel by stabilizing a narrow pore conformation. Hindrance due to R492Q substitution was reported to render D580 and the nearby gate region more flexible so that the pore becomes wider [ 87 ]. While the role of PIP 2 was neglected in this study, it is tempting to combine these findings with R492 as putative PIP 2 binding partner, as observed in the modeled structure [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Later, Cai et al (2021) proposed R492 to interact with D580, imposing autoinhibitory effects on the channel by stabilizing a narrow pore conformation. Hindrance due to R492Q substitution was reported to render D580 and the nearby gate region more flexible so that the pore becomes wider [ 87 ]. While the role of PIP 2 was neglected in this study, it is tempting to combine these findings with R492 as putative PIP 2 binding partner, as observed in the modeled structure [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, TRPV6 inhibition reduces cell migration [ 52 ]. Cai et al found that the TRPV6 pathogenic mutation R532Q enhances the TRPV6/PI3K interaction, thereby activating the PI3K/Akt/GSK-3β cascade to further promote breast cancer migration [ 75 ]. TRPV6 has a strong effect on the proliferation of breast cancer cells, which are regulated by estrogen, progesterone, tamoxifen, and 1, 25-vitamin D3.…”
Section: Trpv6 Expression In Cancermentioning
confidence: 99%
“…TRP channel-related proteins expressed in various cancer cell types such as breast, prostate, lung, colon and pancreatic malignancies, have recently attracted more research attention. Specifically, TRPV6 has been shown to promote the invasion and migration of breast cancer cells ( Cai et al, 2021 ). TRPV6 is linked to cancer cell death and proliferation in prostate cancer ( Lehen kyi et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%